Synthesis of 2,4-Diaryl-2,3-Dihydro-1,5-Benzothiazepines as Antibacterial and Antifungal Agents - barot, V.M.; Patel, M.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
o-Aminophenol reacts with chalcones (I) in methanol and acetic acid to give 3-(2-arninophenylmercapto)-3-amyl-propiophenones (II) which immediately undergo cycIisation in situ to give 2,4-diaryl-2,3-dihydro-1,5- benzothiazepines (IIIa).